Coherence of digital processing of current and voltage signals at decimation for power systems with a large share of renewable power stations - A.L. Kulikov; P.V. Ilyushin; K.V. Suslov; D.N. Karamov (Energy Reports, 2022)
The high energy and environmental performance of renewable power stations (RPS) contributes to their widespread introduction in many countries. A trend towards decentralization of generating capacities and an increase in the share of RPS in their structure brings about the multifactorial features that affect the reliability of power systems. These factors can result in a failure and unnecessary or false operation of intelligent digital devices and systems that perform the protection and automatic control functions. Digital substations using the IEC 61850 protocol to exchange instantaneous values of analog signals employ merging units (MUs) for digital processing of current and voltage. MUs use down-sampling, i.e., decimation, to reduce the number of calculations and meet other purposes. The paper presents findings of an analysis of the digital processing effects associated with the disturbance of coherence of current and voltage signals during decimation. Failure to comply with the coherence requirements during decimation leads to significant errors in the estimates of signal parameters. The extent to which the sinusoidality of signals is distorted due to incoherence can be determined using a normalized cross-correlation coefficient. Simulation results have shown that incoherent sampling enhances the distorting effect for the signals containing high-frequency harmonics and interharmonics. Coherence of digital signal processing after decimation can be ensured by preliminary digital filtering. Superposition of noise components does not affect much the estimations of signal amplitudes during decimation, which are within the allowable error. Coherence of digital processing of current and voltage signals during decimation contributes to the reliable operation of power systems with a large share of RPS, first of all solar photovoltaic and wind power stations.